1999
DOI: 10.1099/0022-1317-80-2-391
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour and papillomavirus exposure in cervical intraepithelial neoplasia: a population-based case-control study.

Abstract: Sexual history is an established risk determinant for cervical neoplasia. It is not clear if human papillomavirus (HPV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 37 publications
5
50
0
1
Order By: Relevance
“…In a previous paper, we have found that HPV-infection explained this association and that sexual history per se thus was not a risk factor (Kjellberg et al, 1999). In this study we detected the well known association between early age of sexual debut and risk for CIN, but again this association lost significance after adjusting for HPV infection.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In a previous paper, we have found that HPV-infection explained this association and that sexual history per se thus was not a risk factor (Kjellberg et al, 1999). In this study we detected the well known association between early age of sexual debut and risk for CIN, but again this association lost significance after adjusting for HPV infection.…”
Section: Discussionsupporting
confidence: 56%
“…b Adjusted odds ratios for HPV seropositivity, smoking and age. c The data on number of lifetime sexual partners has also been published in Kjellberg et al (1999). in the reference category.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a series of validation studies have concluded that only about 50 -70% of genitally infected women (as determined by PCR) will seroconvert (Kirnbauer et al, 1994;Carter et al, 1996;Kjellberg et al, 1999). The reason why HPV serology is not very sensitive for detection of HPV infection is not known.…”
Section: Discussionmentioning
confidence: 99%
“…A serum panel containing serum from 63 children with a mean age of 1.5 years (af Geijersstam et al, 1999) was analysed as a negative control. Samples from 71 adult women, with a mean age of 43 years and with limited sexual experience (70 women with one lifetime sexual partner and one woman with no lifetime sexual partners) were also analysed as negative controls (Kjellberg et al, 1999). After the method was established and validated, 208 serum samples from a nested case-control study of cervical cancer (Lehtinen et al, 1996) were analysed.…”
mentioning
confidence: 99%